ANÁLISE DA INFLUÊNCIA DO SOLO NO DESEMPENHO TÉRMICO DE AMBIENTES SUBTERRÂNEOS EM UMA EDIFICAÇÃO TÉRREA - Resende, Bruna Cristina; Souza, Henor Artur de; Gomes, Adriano Pinto; Cristeli, Pablyne Sant'ana (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Among the several factors that interfere with the thermal performance of buildings, soil temperature is not always considered in thermal performance evaluations. One of the main factors contributing to this scenario is the high complexity of soil consideration in thermal performance analyzes, mainly due to the three-dimensional and transient character of the heat exchange processes involving the soil and the underground walls of a building. However, soil temperature is a factor that influences the final result of heat exchanges in the environment, especially in ground-level buildings. Thus, this work evaluates the soil influence as an active medium in the thermal performance evaluation, adopting as a computational tool the Basement preprocessor of the EnergyPlus software. By using this preprocessor it is possible to analyze the soil influence from the data generated by the program in relation to internal temperatures and losses and heat gains of the environment. Results suggest that when the soil influence is neglected in the thermal analyzes the internal temperature of subterranean rooms increases up to 7.3 ºC when compared to the situation where the soil influence is considered.